2019
DOI: 10.1097/inf.0000000000002344
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ceftazidime-avibactam for the Treatment of Extensively drug-resistant or Pan drug-resistant Klebsiella pneumoniae in Neonates and Children <5 Years of Age

Abstract: Background: Emergence of extensively drug-resistant (XDR) or pan drug-resistant (PDR) Enterobacteriaceae is a major public threat especially for young patients. Treatment options for these bacteria are extremely limited with no safety data existing for neonates and children. Ceftazidime-avibactam has activity against Gram-negative bacteria producing Klebsiella pneumoniae carbapenemase, but virtually no data exist on its use in neonatal and pediatric patients. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 22 publications
2
45
0
5
Order By: Relevance
“…17,23 CZA has been viewed as a valuable antibiotic against CRKP in American and European countries, 18,24 and the administration of CZA appears to be well tolerated and efficacious in pediatric patients. 12,13 In this study, the vitro activity of CZA against CRKP isolated from neonates was 77.7%. Two recent multicenter studies also showed that the vitro activity of CZA against CRKP in adults is high.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…17,23 CZA has been viewed as a valuable antibiotic against CRKP in American and European countries, 18,24 and the administration of CZA appears to be well tolerated and efficacious in pediatric patients. 12,13 In this study, the vitro activity of CZA against CRKP isolated from neonates was 77.7%. Two recent multicenter studies also showed that the vitro activity of CZA against CRKP in adults is high.…”
Section: Discussionmentioning
confidence: 62%
“…While resistance to CZA did not emerge, CZA sensitivity was somewhat lower in a case series of neonates and children <5 years of age patients with CRKP treated with CZA. 13 Resistance emerged in 14% of adult patients with CRKP treated with CZA, 11 and the predominant carbapenemase was KPC. As intestinal carriage of carbapenemase is an important source of transmission, 34 patient-to-patient transmission may be a significant factor in other CZAresistant CRKP isolates in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results from these trials, the Food and Drug Administration (FDA) has recently approved its use in pediatric patients Ͼ3 months of age with complicated intra-abdominal infections (cIAIs), in conjunction with an agent active against anaerobic organisms, and also those with urinary tract infections (UTIs). Currently, clinical data on the treatment of CRE infections with ceftazidime-avibactam in the pediatric population are limited to a few case reports (32,(75)(76)(77)(78).…”
Section: Treatmentmentioning
confidence: 99%
“…Ceftazidime-avibactam has excellent activity against many extended spectrum β-lactamase, Amp-C, KP-carbapenemase and OXA-48 producing enterobacteriaceae; however it is not active against NDM strains [ 2 ]. Aztreonam is effective against NDM strains as NDM cannot hydrolyse aztreonam.…”
mentioning
confidence: 99%